Growth hacking for dummies - Adhiya, Anuj (For Dummies, 2020)
Hack your business growth the scientific way Airbnb. Uber. Spotify. To join the big fish in the disruptive digital shark tank you need to get beyond siloed sales and marketing approaches. You have to move ahead fast-with input from your whole organization-or die. Since the early 2010s, growth hacking culture has developed as the way to achieve this, pulling together multiple talents-product managers, data analysts, programmers, creatives, and yes, marketers-to build a lean, mean, iterative machine that delivers the swift sustainable growth you need to stay alive and beat the competition. Growth Hacking for Dummies provides a blueprint for building the machine from the ground-up, whether you're a fledgling organization looking for ways to outperform big budgets and research teams, or an established business wanting to apply emerging techniques to your process. Written by a growth thought leader who learned from the original growth hacking gurus, you'll soon be an expert in the tech world innovations that make this the proven route to the big time: iteration, constant testing, agile approaches, and flexible responses to your customers' evolving needs. Soup to nuts: get a full overview of the growth hacking process and tools Appliance of science: how to build and implement concept-testing models Coming together: pick up best practices for building a cross-disciplinary team Follow the data: find out what your customers really want You know you can't just stay still-start moving ahead by developing the growth hacking mindset that'll help you win big and leave the competition dead in the water!